Development and Validation of Multidimensional Scales of Public Confidence in Criminal Justice - Pyo, Jimin (Criminal justice review, 2024)
Despite growing interest in public confidence in criminal justice, robust confidence measures have not yet been established. Two studies were conducted to develop multidimensional measures of public confidence in criminal justice. Study 1 involved two-phased construction of scales in which a preliminary inventory was generated and then finalized after psychometric evaluations. Six multidimensional scales (62 items) were constructed for measuring efficiency-, finality-, fairness-, lawfulness-, accuracy-, and transparency-oriented confidence. Study 2 tested the predictive ability of the scale scores for cooperation with criminal justice institutions. Results highlight that higher confidence in authorities’ accurate fact-finding and fair treatment predicted greater willingness to assist institutions. Higher confidence in authorities’ lawfulness predicted greater compliance with the law. The six scales developed are a reliable and valid tool for measuring confidence in criminal justice and predicting cooperation with criminal institutions.